Intramedullary implant exchange and adequate soft tissue coverage in exposed implants following fracture related infection in operatively treated ankle fractures - R.B. Beks; P. van Oosten; D. van Embden; M. Botman; T. Schepers (Trauma Case Reports)
Ankle fractures are common with an increasing incidence due to aging populations. A major complication after surgery for ankle fractures is deep infection, which requires additional treatments and adversely affect long-term outcomes. Treatment of fracture-related infections focuses on achieving fracture union and may involve either retaining or removing the implant, depending on the stability of the implant, with early involvement of a plastic surgeon crucial for adequate tissue coverage. This study presents four cases demonstrating the successful use of intramedullary screw fixation of the fibula to stabilize partially healed fractures, reduce implant load and improve soft tissue coverage in patients with fracture-related infection after operatively treated ankle fractures. Therefore, exchange to intramedullary screw fixation should be considered in patients with fracture related infection of the fibula to reduce the bacterial load of foreign material and allow for better soft tissue coverage and healing.